Somebody is walking on your grave : my cemetery journeys - Enriquez, Mariana (Hogarth, 2025)
"Cemeteries have great stories and sometimes I steal some for my books. Mariana Enriquez has been fascinated by the haunting beauty of cemeteries since she was a teenager. She visits them frequently on her travels around the world, a goth flaneur among the headstones "where dying seems much more interesting than being alive." But when the body of a friend's mother who was disappeared during Argentina's military dictatorship is found in a common grave, Enriquez begins to examine more deeply the complex meanings of cemeteries and where our bodies come to rest. Travel with Enriquez as she journeys across North and South America, Europe and Australia, visiting Paris's catacombs, Prague's Old Jewish Cemetery, New Orleans's above-ground mausoleums, the opulent Recoleta in her hometown of Buenos Aires, and beyond. Enriquez investigates each cemetery's history and architecture, its saints and ghosts, its caretakers and visitors, and, of course, its dead. Weaving personal stories with reportage, interviews, myths, hauntology, personal photographs, and more, Somebody Is Walking on Your Grave is memoir channeled through Enriquez's passion for cemeteries, revealing as much about her own life and unique sensibility as the graveyards she tours. Fascinating, spooky, and unlike anything else, Enriquez's first work of nonfiction, translated by the award-winning Megan McDowell, is as original and startling as the fiction for which she's become so beloved and admired"-- Provided by publisher.